2003
DOI: 10.1103/physrevlett.90.241301
|View full text |Cite
|
Sign up to set email alerts
|

Brane-World Dark Matter

Abstract: We show that, in the context of brane-world scenarios with low tension tau=f(4), massive brane fluctuations (branons) are natural dark matter candidates. We calculate the present abundances for both hot (warm) and cold branons in terms of the branon mass M and the tension scale f. The results are compared with the current experimental bounds on these parameters. We also study the prospects for their detection in direct search experiments and comment on their characteristic signals in the indirect ones.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
220
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 152 publications
(225 citation statements)
references
References 29 publications
3
220
0
2
Order By: Relevance
“…In addition, given the current lack of a dark matter particle detection (both from astrophysical observations and accelerators), it seems worthwhile to further explore modified gravity alternatives. It is worth mentioning that, even if dark matter is a new particle, it might give us some hints about modifications to gravity that could explain cosmic acceleration [179,180].…”
Section: Gravity In Cosmologymentioning
confidence: 99%
“…In addition, given the current lack of a dark matter particle detection (both from astrophysical observations and accelerators), it seems worthwhile to further explore modified gravity alternatives. It is worth mentioning that, even if dark matter is a new particle, it might give us some hints about modifications to gravity that could explain cosmic acceleration [179,180].…”
Section: Gravity In Cosmologymentioning
confidence: 99%
“…This is again the case for some particular supersymmetric, universal extra dimensions or little Higgs models. In this work, however, we point out that the brane-world scenario, originally proposed as a new setting for solving the gauge hierarchy problem [9], is also a viable alternative here.Recently it has been found that massive brane fluctutations (branons) are natural candidates to dark matter in brane-world models with low tension [10,11]. Branon physics can be described at low energies by an effective action which depends essentially on only three parameters: the branon mass M, the brane tension scale f and the cutoff which sets the range of validity of the effective theory.…”
mentioning
confidence: 99%
“…Recently it has been found that massive brane fluctutations (branons) are natural candidates to dark matter in brane-world models with low tension [10,11]. Branon physics can be described at low energies by an effective action which depends essentially on only three parameters: the branon mass M, the brane tension scale f and the cutoff which sets the range of validity of the effective theory.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However there is not evidence of CP T violation in any experiment, and on the contrary, there are important tests that constrain the amount of non conservation of CP T in various sectors of the standard model of particles and interactions. A large number of models have been proposed in literature where CP T violations can be accommodated, as the standard-model extension associated with spontaneous breaking of the Lorentz symmetry in the string theory [4]; spacetime foam models motivated by quantum-gravity (QG) [5]; deformations of special relativity [6] or modified gravity [7]; non-local models originated from string theory [8]; or Lorentz symmetry breaking in extra dimensional models [9].…”
Section: Introductionmentioning
confidence: 99%